2013
DOI: 10.1002/mnfr.201200629
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between aerobic fitness level and metabolic profiles in healthy adults

Abstract: This study demonstrates a relationship between fitness level and the amino acid profile. Moreover, the metabolite changes show that a reduced excretion of amino acids in adults is associated with increased fitness levels and an increased fat oxidation rate during exercise. Interestingly, higher levels of branched chain amino acids were associated with lower fitness levels and higher insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 36 publications
8
56
2
1
Order By: Relevance
“…BCAAs predicted improvements in insulin resistance in patients participating in a weight loss intervention [31,49], and a positive association between BCAAs and insulin resistance has been also reported [34,49]. In the current study, insulin levels were not determined.…”
Section: Discusionmentioning
confidence: 61%
See 1 more Smart Citation
“…BCAAs predicted improvements in insulin resistance in patients participating in a weight loss intervention [31,49], and a positive association between BCAAs and insulin resistance has been also reported [34,49]. In the current study, insulin levels were not determined.…”
Section: Discusionmentioning
confidence: 61%
“…Therefore comprehensive metabolomic data needs to be assessed by bringing together data from different platforms [12,51,54]. A number of nutritional studies have used a gas chromatography/mass spectrometry (GC/MS) based metabolomic approach to analyse fatty acids (FAs) and amino acids (AAs) [34,41] FAs play an important role in metabolic health taking part in many cellular processes, serving as energy reserves or regulating gene expression. Obese subjects report elevated concentrations of serum total FAs, which may have an impact on the development of metabolic syndrome and related disorders [22,50,52].…”
Section: Introductionmentioning
confidence: 99%
“…Morris et al 5 found that amino-acid excretion was reduced in participants with high fitness as indicated by lower urinary levels of amino acids. In contrast, in this previous study also plasma levels of many amino acids were lower in the high fitness group.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2, 3 Furthermore, metabolite levels in body fluids may also reflect consequent phenotypes including cardiorespiratory fitness and obesity. 4, 5, 6, 7 Therefore, targeted metabolomics may particularly help unravel biological mechanisms and identify pathways and networks through which behavioral factors and phenotypes are linked to metabolism. Knowledge about these mechanisms may offer great potential in terms of prevention of chronic diseases, which are strongly linked to human behavior and phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Subjects with complete data were analyzed for this study. Subjects completed one or both of two metabolic challenges; an oral lipid tolerance test (N=120; 54g Fat, 16g Glucose, 550kcal) and an oral glucose tolerance test (N=129; 75g glucose bolus) as described[15, 16]. Serial blood samples were taken for measurement of glucose, insulin and cytokines.…”
Section: Methodsmentioning
confidence: 99%